O'Conner, Image As Artifact - The Historical Analysis Of Film And Television - Reinhartz, Dennis (Teaching History: A Journal of Methods, 1993)
The history of the recorded moving image is but little more than a century old. Yet it has been a century of dynamic change, change in part documented, reflected, and ushered in by development of film and television. The recorded moving image is therefore becoming an important source for historians reconstructing the recent past and equally as important a tool for educators teaching about it.